Histological effects of chronic administration of Phyllanthus amarus on the kidney of adult Wistar rat - Adjene, Josiah Obaghwarhieywo (Medknow Publications & Media Pvt Ltd, 2010)
BACKGROUND: Phyllanthus amarus is commonly used for treatment such as in gastro, urogenital diseases and infection. However, it is speculated to have some toxic effects such as renal tubular damage. AIMS: This study was to investigate the histological effects of chronic administration of the herb on kidney of adult Wistar rats. MATERIAL AND METHODS: Rats of both sexes (n = 24), with average weight of 200g were randomly assigned into two treatments (A and B) and control (C) groups of 8 rats each. Rats in treatment groups (A) and (B) respectively received daily administration of 400mg and 800mg of aqueous Phyllanthus amarus, per 70kg body weight for 30days through the orogastric tube. The control group received distilled water through the same route. All rats were fed with grower's mash and given water liberally. The rats were sacrificed by cervical dislocation on the thirty-first day of the experiment and the kidneys were carefully dissected out and quickly fixed in 10% formal saline for histological study. RESULTS: The observations indicate that rats in the treated groups showed some varying degree of distortion and disruption in microanatomy of the kidney including interstitial oedema and tubular necrosis, when compared to the control section. CONCLUSION: This report provides further evidence that medicinal use of Phyllanthus amarus has a potential adverse effect. This warrants further studies to establish or rule out any untoward side-effect of chronic renal dysfunctions.